2022 IEEE International Conference on Software Analysis, Evolution and Reengineering (SANER) 2022
DOI: 10.1109/saner53432.2022.00101
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effectiveness of Clustering for Story Point Estimation

Abstract: Automated techniques to estimate Story Points (SP) for user stories in agile software development came to the fore a decade ago. Yet, the state-of-the-art estimation techniques' accuracy has room for improvement.In this paper, we present a new approach for SP estimation, based on analysing textual features of software issues by employing latent Dirichlet allocation (LDA) and clustering. We first use LDA to represent issue reports in a new space of generated topics. We then use hierarchical clustering to agglom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This has led to numerous studies over the years to help with effort estimation and improve the accuracy of effort estimation using Machine Learning algorithms. Several of these studies have been trying to uncover automated ways of story points effort estimation for tasks based on certain features with the intention of averting incorrect effort estimations due to subjectivity and bias resulting from human judgement, along with, and more essentially to an agile team, yielding consistent estimates across different sprints and releases and the overall project's lifecycle [3].However, there are no reviews which focus of the use of Deep Learning algorithms with special focus on story points effort estimation. The unavailability of appropriate information, metrics as well as past experiences around work item effort estimation can surely lead to imprecision issues.…”
Section: Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…This has led to numerous studies over the years to help with effort estimation and improve the accuracy of effort estimation using Machine Learning algorithms. Several of these studies have been trying to uncover automated ways of story points effort estimation for tasks based on certain features with the intention of averting incorrect effort estimations due to subjectivity and bias resulting from human judgement, along with, and more essentially to an agile team, yielding consistent estimates across different sprints and releases and the overall project's lifecycle [3].However, there are no reviews which focus of the use of Deep Learning algorithms with special focus on story points effort estimation. The unavailability of appropriate information, metrics as well as past experiences around work item effort estimation can surely lead to imprecision issues.…”
Section: Rationalementioning
confidence: 99%
“…Agile teams generally rely on using Story Points as the unit of measure [3], for estimating the combined effort required by each user story, thereby relying on expert-based estimation, with additional buffers for any uncertainty or added complexity within those user stories [4]. As opposed to traditional approaches which aimed at estimating the whole project, estimation using story points gauges the required effort for each individual user story or feature.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the accuracy of the models, we measure the Standardized Accuracy (SA). In particular, SA measures how well our models can estimate the development time in comparison to random guessing (Sarro et al 2016;Tawosi et al 2021)…”
Section: Analyzing the Modelsmentioning
confidence: 99%
“…Latent Dirichlet Allocation (LDA)-based classifier: A recent study showed that LDAbased classifiers can be used to predict the SP (Tawosi et al 2022). Hence, we used LDA-based classifier as our baseline to evaluate whether our classifier can outperform a classifier built based on the topics extracted from natural language text.…”
Section: Fig 6 An Overview Of the Calculation Approach For The Text D...mentioning
confidence: 99%
See 1 more Smart Citation